Antigenic and genetic characterization of Streptococcus pneumoniae strains isolated from patients with invasive and non-invasive pneumococcal infections by using high-throughput sequencing - K. O. Mironov; I. I. Gaponova; V. I. Korchagin; Yu. V. Mikhailova; A. A. Shelenkov; V. V. Kaptelova; A. N. Chagaryan; N. V. Ivanchik; R. S. Kozlov (Журнал микробиологии, эпидемиологии и иммунобиологии, 2021)
The objective of this study was to characterize and compare antigenic and genetic characteristics of Streptococcus pneumoniae strains isolated from patients with invasive and non-invasive pneumococcal infections (PIs) by using the data of high-throughput sequencing.Materials and methods. A total of 158 S. pneumoniae strains were studied. All of them were isolated during different stages of the PEHASus multicenter study performed in 2015-2020. The data analysis was based on the information about whole-genome sequences of 46 strains isolated during the above study. Real-time PCR methods and high-throughput sequencing (the Illumina platform) were used for identification of serotypes. The SeroBA, PneumoCaT software and PubMLST.org website resources were used in the data processing.Results and discussion. The serotypes of all the studied strains were identified. A number of discrepancies among serotypes in serogroup 6 and one discordant result were revealed by the analysis of whole-genome sequences using 2 programs. The PCR methods were effectively used to characterize serotypes in 87% and 69% of the pathogens of invasive and non-invasive PIs, respectively. The serotypes contained in PCV13 accounted for 59% and 37%, while PPV23 serotypes accounted for 78% and 53% of the strains isolated from patients with invasive and non-invasive PIs, respectively. The data analysis was unable to identify either the dominant sequence type (a total of 81 sequence types have been identified) or clonal complexes, except for serotype 3 strains, thus demonstrating consistency with the data from previous studies suggesting the absence of a well-represented clonal structure of S. pneumoniae associated with pneumococcal meningitis in Russia.Conclusion. The obtained data made it possible to identify the distribution of the circulating serotypes and genetic characteristics of the strains isolated from PI patients, thus being instrumental for assessment of the effectiveness of the existing polyvalent vaccines and providing information for improvement of the PCR-based methods of serotyping.